Wave drag on asymmetric bodies. (4th September 2019) - Benham, G. P.; Boucher, J. P.; Labbé, R.; Benzaquen, M.; Clanet, C.
Abstract : An asymmetric body with a sharp leading edge and a rounded trailing edge produces a smaller wave disturbance moving forwards than backwards, and this is reflected in the wave drag coefficient. This experimental fact is not captured by Michell's theory for wave drag (Michell Lond. Edinb. Dubl. Phil. Mag. J. Sci., vol. 45 (272), 1898, pp. 106–123). In this study, we use a tow-tank experiment to investigate the effects of asymmetry on wave drag, and show that these effects can be replicated by modifying Michell's theory to include the growth of a symmetry-breaking boundary layer. We show that asymmetry can have either a positive or a negative effect on drag, depending on the depth of motion and the Froude number.